Investigate the relationship between knowledge management and organizational commitment among staff of Khaje Nasir Toosi University of Technology - SAMANIAN, MOSAYYEB (Qualitative and Quantitative Methods in Libraries, 2022)
Today, knowledge is known as a key valuable competitive asset, which is the basis for sustainable growth and a key to sustainable competitive advantage in an organization. So knowledge and human capital management must be considered as a key factor in any activity. This study has been done aimed to investigate the relationship between knowledge management and organizational commitment among the employees of Khajeh Nasir University in Tehran. This study is applied in terms of goal and in terms of descriptive method in the correlation type. The target population included all employees of Khajeh Nasir University in Tehran, and according to Kerjecie and Morgan table, 100 individuals were selected randomly and of proportional stratified type. Research tools included Probst et al (2000)'s standard questionnaires of knowledge management, and endemic questionnaire of Allen and Meyer (1997), whose reliability was measured using Cronbach's alpha coefficient 0.942 for knowledge management questionnaire and 0.716 for commitment. The research data were analyzed by the software 19 SPSS, using Pearson's correlation coefficient in descriptive and inferential statistics using the Kolmogorov-Smirnov test. Comparing the 74% significance level obtained with a coefficient error of 0.50 can be concluded that there is no significant relationship between knowledge management and normative commitment, and there is no significant relationship between knowledge management and continuous commitment and affective commitment, except knowledge and affective commitment sub-indexes.